ENVIRONMENTAL CLEANLINESS AS A PORTAL TO PUBLIC HEALTH IN HALLMARK III VILLAGE KEDUNGJAYA DISTRICT, KEDAWUNG REGENCY CIREBON - M. Anissul Fata; Winda Dwi Yanthi; Gian Fitralisma; Rohmatul Fawaiz; Yeyet Daryati; Ellin Herlina; Dedi Surono; Surya Firdaus (Jurnal Abdisci, 2025)
Abstract: Background. Real Work Lecture (KKN) has transformed, focusing on community empowerment and sustainable development. KKN provides benefits for students, the community, and universities. Methods. In Dusun III, Kedungjaya Village, STIE KKN students carried out a community service program, cleaning the environment and increasing awareness of cleanliness. Result. As a result, the environment is cleaner, social relations improve, and the risk of disease decreases. Conclusion.This activity instills the values of mutual cooperation and environmental awareness, proving the positive synergy between students, the community, and universities in advancing the village. Implementation. Mutual cooperation activities organized by KKN students in Dusun III, Kedungjaya Village has succeeded in achieving its main objective, namely creating a healthy environment. which is cleaner and healthier. Through the active involvement of students, village officials, and local community, this activity not only improves environmental cleanliness, but also strengthen social relations between residents.